Mapping hazard risk: A case study of Ubatuba, Brazil - Guerra, Antonio José Teixeira; Oliveira Jorge, Maria do Carmo [UNESP] (My University, 2009)
Steep slopes in subtropical zones are always at risk from landslides. The risk greatly increases when there is rapid, unplanned urban growth. This has happened at Ubatuba on the Brazilian coast - tourism-related development has forced local people into narrow valleys with steep slopes. In this article the authors describe how the hazard risk can be mapped, helping the local authorities to control the problem.
Keywords: disaster management; hazard assessment; landslide; mapping method; risk assessment; slope failure; Brazil; Sao Paulo [Brazil]; South America; Ubatuba